تطبيق طريقة شرفة المسرح والجلسة فى تعليم اللغة العربية لترقية مهارة الكلام بمدرسة الثانوية المحفوظة - Labibatul Fachiroh; Muhammad Thohir (Universitas Yudharta Pasuruan, 2020)
The title of this research is to apply the gallery session method in Arabic learning to improve speaking skills at the Madrasah Al-Machfudzoh Sidoarjo. Discuss how the implementation of the method in Madrasah Al-Machfudzoh and its superiority in increasing students' speaking skills. Here, the researcher examines the extent of the role of the application of the gallery session method in Madrasah Al-Machfudzoh, especially the 7th-grade Tsanawiyah, to improving the speaking skill. Here the researchers used descriptive qualitative methods. This research is library research that relies on a descriptive-analytical approach (al-manhaj al-washfi at-tahlili). The descriptive approach is to analyze scientific material that is related to the subject, through library research and then presented and explained systematically. The results of this study show that the gallery session method has many advantages. Students are trained to understand the contents of reading and then be able to visualize it in the form of images to express it with communicative language then.